2006
DOI: 10.1038/sj.bjp.0706656
|View full text |Cite
|
Sign up to set email alerts
|

Vanilloid VR1 receptor is involved in rimonabant‐induced neuroprotection

Abstract: 1 Recently, a potential neuroprotective effect of rimonabant, independent of the CB 1 receptor interaction, has been proposed. In the present study, the role of transient receptor potential channel vanilloid subfamily member 1, named VR 1 , on neuroprotective effect of rimonabant, on global cerebral ischemia in gerbils, was investigated. 2 Rimonabant (0.05-3 mg kg À1 ), given i.p. 5 min after recirculation, dose dependently antagonized the ischemia-induced decrease in electroencephalographic (EEG) total spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 52 publications
(90 reference statements)
2
47
0
Order By: Relevance
“…Although the exact mechanisms of the bell-shaped doseresponse curves remain to be elucidated, it could be speculated that interactions with other cannabinoid receptors might be involved. 17,20,27,28 As previously reported, 17 lack of CB2R expression did not affect infarct outcome. It has been reported that no significant changes in N-arachidonoylethanolamine, one of the main endogenous cannabinoid agonists, was seen after 4, 12, or 24 hours of pMCAO in mice (reviewed in 6 ).…”
Section: Discussionsupporting
confidence: 73%
“…Although the exact mechanisms of the bell-shaped doseresponse curves remain to be elucidated, it could be speculated that interactions with other cannabinoid receptors might be involved. 17,20,27,28 As previously reported, 17 lack of CB2R expression did not affect infarct outcome. It has been reported that no significant changes in N-arachidonoylethanolamine, one of the main endogenous cannabinoid agonists, was seen after 4, 12, or 24 hours of pMCAO in mice (reviewed in 6 ).…”
Section: Discussionsupporting
confidence: 73%
“…TRPV1 receptors are activated by changes in temperature and pH as well as AEA and lipoxygenase products that accumulate during ischemia and can contribute to excitotoxicity [103]. Although the mechanism of this effect of rimonabant is unclear (see discussion section of [102] for a thorough discussion of the possibilities), this study provides strong support for a neuroprotective effect of the drug against ischemic/reperfusion injury.…”
Section: Evidence That Reduced Endocannabinoid Signaling Is Protectivmentioning
confidence: 72%
“…In one of these studies [30], a second, structurally unrelated CB1 receptor antagonist, LY 320135 [101], was also protective. Rimonabant is also protective in male gerbils exposed to transient, global ischemia [102]. The drug, administered 5 min after reperfusion and at low doses (less than 0.5 mg/kg), protected against the development of behavioral and EEG changes; in addition, animals given rimonabant exhibited nearly complete survival of cells in the CA1 region of the hippocampus 7 days after the ischemia.…”
Section: Evidence That Reduced Endocannabinoid Signaling Is Protectivmentioning
confidence: 98%
“…However, administration of rimonabant still stimulates neurogenesis and induces cannabinoid-like effects in mice deficient in cannabinoid 1 receptors (Jin et al, 2004;Wiley et al, 2012), indicating the involvement of additional targets. Indeed, the neuroprotective effect of rimonabant requires the vanilloid receptor VR1, independent of the CB 1 R interaction (Jin et al, 2004;Pegorini et al, 2006). These biarylpyrazole compounds also appear to have targets other than CB 1 R, CB 2 R, and VR1 (Raffa and Ward, 2012); for example, AM251 and rimonabant are agonists of GPR55, a recently deorphanized G protein-coupled receptor that is expressed in peripheral tissues and is positively associated with obesity in human (Moreno-Navarrete et al, 2012).…”
Section: Introductionmentioning
confidence: 99%